EVALUASI SISTEM PREMI PANEN TERHADAP KINERJA KARYAWAN PANEN PADA PERKEBUNAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI PT. SENTOSA KALIMANTAN JAYA - Barmas Indah Sari; Rusli Anwar; Rusmini (JURNAL AGRIMENT, 2020)
This research is motivated by the company imposing a premium system on harvest employees with the aim of encouraging harvest employees to work even harder, so as to provide results in increasing the quality and quantity of harvest which will result in profits for the company. Therefore the aim of this research is to be able to evaluate the harvest premium system on the performance of oil palm harvest employees and to identify the characteristics of harvest employees in the Afdeling scope of an oil palm plantation company. The research method used is to take primary data in the form of observations and observations, field data, documentation, questionnaires and secondary data in the form of documents from the company with the sample method is the Slovin formula which is done randomly with the number of respondents 26 harvest employees then process the data using rock microsoft office. The data analysis method used is a simple descriptive statistical method using the data and information obtained and the Likert scale. The results of this study indicate that the harvest premium system implemented by PT. Sentosa Kalimantan Jaya (SKJ) is already good and has become a motivation for harvesters to work productively with results that can exceed the base or harvest target set by the company. On average, the harvester was able to harvest 255 jugs / person while the base was 135 for Afdeling 4 and the average harvester was able to harvest 245 jubils / person while the base was 135 for Afdeling 5, the difference was thought to be due to differences in the abilities of each worker. , differences in land conditions and crops harvested. Characteristics of respondents related to the performance parameters of harvest employees, from the age factor that is dominated is the productive age of 20-40 years in terms of working, the sex of harvest employees as a whole is male as many as 26 respondents, the majority of harvest employees are educated at elementary school (elementary school) Most of the existing employees also have sufficient 2-4 years of experience, this is a sufficiently supportive factor for the success of harvest employees. Harvest employee performance of PT. Sentosa Kalimantan Jaya (SKJ) has performed very well (4.76) due to quantity, quality, timeliness and attendance.